2015
DOI: 10.3097/lo.201541
|View full text |Cite
|
Sign up to set email alerts
|

The appreciation of nature and landscape by tourism service providers and visitors in the Ore Mountains (Germany)

Abstract: The paper presents empirical studies on the appreciation of nature and landscape in the Eastern Ore Mountains (Saxony, Germany) by tourism service providers (TSP) and visitors. Attractive landscape and experience of nature are the most important reasons to visit this region and to spend leisure time there. Particularly mountain meadows, raised bogs and mixed forests are highly appreciated. Deforestation, industrial development and the decline of biodiversity would reduce attractiveness for visitors. We also as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 49 publications
3
31
0
4
Order By: Relevance
“…The respondents justified their responses mostly based on the attractions these landscapes have to offer, and especially those connected to the natural dimension of the landscape. This outcome accords with long-standing, broadly held lay conceptualizations of landscape, where its natural dimension predominates (Bastian et al 2015). The outcome also accords with both the principal and the more specific tourism motives in our case studies, all of which place an emphasis on nature -whether they refer to seaside tourism (3Ss), or upland tourism (forests, national parks, ponds, etc.…”
Section: Understanding and Conceptualization Of Tourist Landscapesupporting
confidence: 85%
“…The respondents justified their responses mostly based on the attractions these landscapes have to offer, and especially those connected to the natural dimension of the landscape. This outcome accords with long-standing, broadly held lay conceptualizations of landscape, where its natural dimension predominates (Bastian et al 2015). The outcome also accords with both the principal and the more specific tourism motives in our case studies, all of which place an emphasis on nature -whether they refer to seaside tourism (3Ss), or upland tourism (forests, national parks, ponds, etc.…”
Section: Understanding and Conceptualization Of Tourist Landscapesupporting
confidence: 85%
“…Sali et al [16] found that a relationship between high real estate values and the presence of agricultural mountain landscape exists. As part of the multifunctionality of farms and landscape valorization, the maintenance of human influence, biodiversity-rich, so called semi-natural ecosystems as pastures and mountain meadows must be guaranteed, but this surely needs considerable financial means [17].…”
Section: Introductionmentioning
confidence: 99%
“…This value was based on an average value calculated from a literature review for a study in Remscheid [56]. This amount fits well to an estimated daily price for a membership in a gym in the Munich area or within the WTP range described in a study from the Ore Mountains for a day ticket to visit an area of high nature conservation value [57].…”
Section: Methodsmentioning
confidence: 95%